SAKARIFIKASI SERAT TANDAN KOSONG DAN PELEPAH KELAPA SAWIT SETELAH PRETREATMENT MENGGUNAKAN KULTUR CAMPURAN JAMUR PELAPUK PUTIH Phanerochaete chrysosporium dan Trametes versicolor - Euis Hermiati; Lucky Risanto; Sita Heris Anita; Yosi Aristiawan; Yanni Sudiyani; Ahmad Hanafi; Haznan Abimanyu (Jurnal Penelitian Hasil Hutan, 2014)
There are only a few studies conducted on the use of co-culture of white-rot fungi for pretreatment of lignocellulosic biomass. The aim of this research is to study the effects of biological pretreatment of oil palm empty fruit bunch (OPEFB) and oil palm frond (OPF) fiber using co-culture of two white-rot fungi, namely Phanerochaete chrysosporium and Trametes versicolor, on the results of the enzymatic saccharification of such biomass. The representative samples of OPEFB and OPF fibers (40-60 mesh in sizes) after being sterilized, each as much as 5% (w/v), were inoculated with the co-cultures of the two fungi and incubated at ±27°C for 4 weeks. The samples were taken partially and then examined after 1, 2, 3, and 4 weeks of incubation. Saccharification process using cellulase and β-glucosidase was performed in a water bath shaker at 50°C for 48 hours. Reducing sugar, glucose and xylose content were analyzed. The highest reducing sugar yield, glucose and xylose concentrations from the saccharification on OPEFB, as much as consecutively 13.08%, 0.86 mg/g and 0.13 mg/g, were obtained after pretreatment for 4 weeks; while likewise those for OPF corresponding to 8.98%, 0.92 mg/g and 0.23 mg/g, respectively, were obtained after 2-week pretreatment.